Validity and interobserver agreement of a new radiographic grading system for intervertebral disc degeneration: Part II. Cervical spine - Kettler, Annette (Springer-Verlag, 2006)
A new radiographic grading system for a more objective assessment of lumbar intervertebral disc degeneration has been described and tested in Part I of this study. The aim of the present Part II of the study was to adapt this system to the cervical spine, and to test it for validity and interobserver agreement. Some modifications of the grading system described in Part I were necessary to make it applicable to the cervical spine. Its basic structure, however, stayed untouched. The three variables “Height Loss”, “Osteophyte Formation” and “Diffuse Sclerosis” first have to be graded individually. Then, the “Overall Degree of Degeneration” is assigned on a four-point scale from 0 (no degeneration) to 3 (severe degeneration). For validation, the radiographic degrees of degeneration of 28 cervical discs were compared to the respective macroscopic ones, which were defined as “real” degrees of degeneration. The interobserver agreement was determined between one experienced and one unexperienced observer using the radiographs of 57 cervical discs. Quadratic weighted Kappa coefficients (κ) with 95% confidence limits (95% CL) were used for statistical evaluation. The validation of the new version of the radiographic grading system showed a moderate agreement with the “real”, macroscopic overall degree of degeneration (κ=0.599, 95% CL 0.421–0.786). In 64% of all discs the “real” overall degree of degeneration was underestimated but never overestimated. This underestimation, however, was much less pronounced and the Kappa coefficients were significantly higher for the three variables: Height Loss, Osteophyte Formation, and Diffuse Sclerosis separately. The agreement between the radiographic ratings of the experienced and the unexperienced observer was substantial for the overall degree of degeneration (κ=0.688, 95% CL 0.580–0.796), almost perfect for the variable, Height Loss, moderate for Osteophyte Formation and fair for Diffuse Sclerosis. In conclusion, we believe that the new version of the radiographic grading system is a sufficiently valid and reliable tool to quantify the degree of degeneration of individual cervical intervertebral discs. In comparison to the version for the lumbar spine described in Part I, however, a slightly higher tendency to underestimate the “real” overall degree of degeneration and somewhat higher interobserver differences have to be expected.